Identity, Immigration and Adolescence: A Proposal for Identity Components for Adolescents of Immigrant Origin in Spain - Mir Gual, Andreu (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
The article is presented with the objective of establishing a proposal of identity components for adolescents of immigrant origin in Spain. Specifically, we have worked with people from three different origins such as Argentina, Morocco and China. The process of data collection and analysis has been developed following the framework established by qualitative research models, using three main information collection strategies: observation, semi-structured interviews and discussion groups. The presence of identitarian meanings from the country of origin tends to be intermingled with others more typical of the host society, which adds a certain complexity to identity-building processes already marked by adolescence itself. It is on the basis of this double transition (cultural and vital) that this research focuses.